Insights into the impacts of autotoxic allelochemicals from rhizosphere of Atractylodes lancea on soil microenvironments - Wang, Meng; Deng, Juan; Duan, Gonghao; Chen, Lei; Huang, Xiao; Wang, Wenjie; Gong, Ling; Zhang, Yan; Yu, Kun; Guo, Lanping (Frontiers in Plant Science, 2023)
Atractylodes lancea suffers from continuous cropping obstacles that have become a major constraint in its cultivation, but there is still little information on the autotoxic allelochemicals and their interaction with soil microorganisms. In this study, we firstly identified the autotoxic allelochemicals from rhizosphere of A. lancea and determined their autotoxicity. Third-year continuous A. lancea cropping soils, i.e., rhizospheric soil and bulk soil, compared with control soil and one-year natural fallow soil were used to determine soil biochemical properties and microbial community. Eight allelochemicals from A. lancea roots were detected and exhibited significant autotoxicity effects on seed germination and seedling growth of A. lancea with the highest content of dibutyl phthalate in rhizospheric soil and lowest IC50 value of 2,4-di-tert-butylphenol inhibiting seed germination. The contents of soil nutrients and organic matter, pH value, and enzyme activity were altered between different soils, and the parameters of fallow soil were close to those of the unplanted soil. The PCoA analysis indicated that the community composition of both bacteria and fungi were differed significantly among the soil samples. Continuous cropping decreased OTUs numbers of bacterial and fungal communities, and natural fallow restored them. The relative abundance of Proteobacteria, Planctomycetes, and Actinobacteria decreased, and that of Acidobacteria and Ascomycota increased after three years cultivation. The LEfSe analysis identified 115 and 49 biomarkers for bacterial and fungal communities, respectively. The results suggested that natural fallow restored the structure of soil microbial community. Overall, our results revealed that autotoxic allelochemicals caused the variations of soil microenvironments and resulted in replantation problem of A. lancea, and natural fallow alleviated the soil deterioration by remodeling the rhizospheric microbial community and restoring soil biochemical properties. These findings provide important insights and clues for solving the continuous cropping problems and guiding the management of sustainable farmland.